Design and Build Online Store Website bicycle store KawanKita - Eddy Sukamto; Albertus Dwiyoga Widiantoro; Erdhi Widyarto Nugroho (Soegijapranata Catholic University, 2023)
E-commerce websites are important to implement in small business processes. To facilitate the transaction process, this research was carried out so that the transaction process between sellers and buyers became more effective and efficient. The purpose of this research is to attract consumers with an attractive and user-friendly website to buy products from the KawanKita bicycle shop so that it has an impact on increasing sales, the analytical method process is applied to implementation. The development method used is